External cantilever sling in septorhinoplasty: A new technique - (:unkn) unknown (WILLIAMS & WILKINS, 1997)
The nose is by far the most important aesthetic complex of the face, Neither appearance nor function is expendable, and both should be considered together when nasal surgery is planned. Surgical correction of the deviated nose associated with a twisted and severely deviated septum is therefore a very difficult surgical challenge, The dilemma of the surgeon is to fashion a stable and aesthetically pleasing nose together with restoration af the airway on both sides. Development of mucoperichondrial and mucoperiosteal flaps bilaterally, total removal of the deviated septum, straightening it outside, followed by replacement as a free graft constitute an option in treatment of the severely deviated nose. Although King and Ashley(1) described the total removal of the deviated septum in a single piece to correct such severe nasal deviations for the first time, the principles and indications of this technique were established and published in detail by Rees.(2) Positioning and stabilization of the septal cartilage in this technique may prove insufficient in the majority of such septorhinoplasty patients, in whom both nasal hones are also immobilized, Fear of collapse of the nasal dorsum, which is likely to occur, after 1 replacement of septal cartilage as a free transplant has led me to develop the technique presented here: the external cantilever sling.
Keywords: SEPTUM